Alchemy in un mundo al revés: Gold, “Raw Law” and Indigenous Law in Colombia’s armed conflict - Viviane Weitzner (Cahiers des Amériques Latines)
Using the concept of alchemy as a conceptual backbone, this article explores the effects of diverse legal pluralities on the Embera Chamí Indigenous people living in the gold-rich ancestral homeland of the Resguardo Indígena Cañamomo Lomaprieta in Caldas, Colombia. Drawing on ten years of collaborative research and ethnography, I develop a concept I call “Raw Law,” the law of outlawed, armed actors and their norms, sanctions and modus operandi, contributing insights that push conceptual boundaries and add complexity to analyses of “the law.” I show the “inter-il-legalities” at work, as the Embera Chamí exercise their own law over their self-named and centuries-old “ancestral mining,” as a counter-proposal and exercise of self-determination in the face of State Law that criminalizes this gold mining and attempts to impose unilaterally developed formalization schemes. I tease out the effects of “nefarious alchemical” technologies deployed to erode the Embera Chamí land base and constrain their autonomy and decision-making, highlighting the “positive alchemies” the traditional authorities use to assert their self-government and push for their rights to be upheld. I consider the types of transnational flows intruding on the Embera Chamí and what this distinct and violent context means for analysis through the lens of legal pluralities in Colombia, Latin America, and beyond.